2014
DOI: 10.1159/000364828
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Glutamate Levels in Schizophrenia: Evidence from a Meta-Analysis

Abstract: Background: Recent research attempting to develop novel medications has turned to glutamatergic signaling pathways to find effective treatments for symptom clusters of schizophrenia. This meta-analysis was undertaken to clarify whether a difference in peripheral glutamate levels exists between patients with schizophrenia and healthy controls. Methods: The electronic databases Ovid MEDLINE, PubMed, and PsycINFO were systematically searched up to April 2013. The search was limited to case-control studies of bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
3
13
2
3
Order By: Relevance
“…The result is compatible with previous reports, which showed increased serum levels of glutamate in chronic schizophrenia patients 28, 29 . A couple of reports have attempted and failed to replicate these findings 30, 31 ; however, a recent meta-analysis confirmed that the peripheral glutamate level of schizophrenia subjects was significantly higher than that of HC 24 . While these are findings pertain to chronic schizophrenia, we found increased glutamate levels in FEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is compatible with previous reports, which showed increased serum levels of glutamate in chronic schizophrenia patients 28, 29 . A couple of reports have attempted and failed to replicate these findings 30, 31 ; however, a recent meta-analysis confirmed that the peripheral glutamate level of schizophrenia subjects was significantly higher than that of HC 24 . While these are findings pertain to chronic schizophrenia, we found increased glutamate levels in FEP.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral glutamatergic amino acids have been investigated in patients with schizophrenia 23, 24 and a meta-analysis showed that peripheral glutamate levels in schizophrenia patients were significantly higher than those in controls 24 . This is consistent with a prevalent model of hyperglutamatergic state in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies focused on peripheral glutamate levels in people with Sz. In a metaanalysis [86] of 10 studies, higher levels (standardized mean difference = 0.64; 95%CI = 0.21-1.06) of glutamate have been reported in blood from people with Sz compared to controls, however, similar dysregulations have been reported in the small number of studies that focused on major depressive disorder [90,91] , suggesting the alteration of glutamate levels is not specific to the diagnosis of Sz. Interestingly, the response of platelet intracellular calcium to glutamate was greater in people with Sz than in controls, suggesting NMDA receptor may be more sensitive in these people [87] .…”
Section: Glutamatergic Pathwaysmentioning
confidence: 96%
“…10). According to this model, the fact that some carriers are susceptible to meningococcal diseases while others are not might be partly explained by variations in the glutamate concentrations in the blood, which are affected by many factors (45,(50)(51)(52). However, reduction of the glutamate concentrations beneath meningococcal colonies on HBMEC could not be directly proven, and further examinations should be performed when an in vivo molecular probe for glutamate becomes available.…”
Section: Discussionmentioning
confidence: 99%